Low Dose Radiation Therapy for COVID 19: benefit or threat? - Almanie, Ahlam; Abbasi, Samaneh (Journal of Liaquat University of Medical & Health Sciences, 2021)
The new coronavirus outbreak emerged at the end of 2019 worldwide in a very short period of time. The number of victims of this virus until 2020/11/17 has been 1323143. The consequences of these viruses in humans are common cold or mild illness in the upper respiratory region. In more severe cases can causes severe interstitial pneumonia and acute respiratory distress syndrome (ARDS) and Middle East respiratory syndrome (MERS) and, severe acute respiratory syndrome (SARS). So far various drugs have been prescribed and used for the treatment. However, their efficiency and their side effects for treatment of pneumonia of COVID19 are unknown and should be more investigated. Low-dose radiation (LDR) (30 to 100 cGray(Gy)) has been used historically since the early 1930s with hopeful results for pneumonia treatment and was a common treatment solution for viral pneumonia until the 1940s. As some recent studies have raised the use of LDRT for COVID19 treatment, we sought to review previous evidence of therapeutic role of LDRT in the inflammatory diseases as well as recent recommendations about consider LDRT as the treatment method for COVID19. Based on the available evidence and the background of studies, it seems that choosing a dose 0.3-0.5 Gy in severe cases of the disease, as well as using radiation for the whole body instead of the lungs, can optimize the immune system, and optimizing the immune system will help improve COVID-19